Insulin resistance and significance of postprandial lipid profile in normoglycemic coronary artery disease - Mookambika, R V; Rajendiran, Rajendiran; K., Jayachandran; Aruna, Aruna (International Journal of Medical Research and Review, 2017)
Background: Coronary artery disease is a continuum of a pathological process, in which the coronary arteries gradually thicken, harden and atherosclerotic plaques develop which further occludes the blood flow. The prevalence of coronary artery disease is rapidly rising in India. There are various risk factors of CAD which have been extensively studied, out of which Type-2 diabetes is an important etiopathogenic factor of accelerated CAD. Insulin resistance plays an important role in the pathogenesis of the development of type- 2 diabetes. Despite the clear relationship between type-2 diabetes and CAD, the association of insulin resistance and CAD is more obscure in people without diabetes. Aims & Objectives: To find the association between insulin resistance and Coronary artery disease, to evaluate the role of postprandial lipid profile and its relationship with development of CHD and the evaluation of apolipoproteins (a and b) on the same group. Subjects and Methods: Fifty patients of coronary artery disease admitted to ICCU/CCU of psg institute of medical sciences and research were studied. The cases of this present study were 50 non diabetic CAD patients and controls were selected based on age and sex matched non diabetic ‘and non CAD patients who has to undergo similar set of investigations as cases to find out association of insulin resistance by using HOMA score and to find out the significance in abnormalities of postprandial lipid profile in these patients. Results: 92% of the cases had insulin resistance, 52% of the controls had normal HOMA score when compared to cases. Apolipoprotein b was significantly elevated in cases (84%) than controls. All patients were normoglycemic. Serum triglycerides were significantly high in cases than controls in both fasting and postprandial states. Conclusion: Improving insulin sensitivity would offer substantial benefits by decreasing the morbidity, mortality, and economic burden associated with CAD especially in the country like India